A method for determining the characteristics and process parameters of ion adsorption type rare earth leaching
Through continuous droplet leaching method, the concentration of rare earth leaching agent is determined and combined with the determination of zeta potential, pH value and conductivity value, the problems of long process, high consumption and large errors in the determination of leaching conditions in the prior art are solved, and the rare earth leaching is realized Improve efficiency and assessment of tailings stability have reduced wastewater generation and soil erosion.
Patent Information
- Application Number
- CN202111236185.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-22
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-10-22
AI Technical Summary
In the existing ion adsorption rare earth leaching process, the process of determining leaching conditions is long, consumes a lot, and has a large error, and it is difficult to effectively reduce wastewater generation and soil erosion.
The concentration of leaching agent was determined by continuous dropping method. By dispersing the original rare earth mineral sample in aqueous solution and immersing the leaching agent solution several times until the increase in the rare earth concentration of the supernatant liquid is less than 1%, it is determined. Optimal leaching agent concentration and combined with the determination of zeta potential, pH and conductivity, leaching conditions are optimized to reduce wastewater generation and evaluate tailings landslide risks.
The leaching process is achieved, which reduces experimental errors and soil erosion, improves the rare earth leaching efficiency and tailings stability, and can effectively evaluate the optimal concentration range of leaching reagents and the risk of tailings landslides.
Smart Images

Figure CN114323828B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rare earth hydrometallurgy and environmental protection, and relates to a process for selecting a leaching agent in an ion adsorption type rare earth leaching process and evaluating the correlation between the leaching agent and mineral characteristics and the risk of tailings landslide. Background Art
[0002] In the decades since the mining of ion-adsorbed rare earths, scientific researchers have conducted a lot of research on leaching conditions. The previous 50 years of research has been detailed in the book "Ion-Adsorbed Rare Earth Resources and Their Green Extraction". In all studies, mineral characteristics and the selection of leaching reagents are the most important contents. In the study of selecting leaching agents, the most common practice is the column elution method. This method has a large workload, and the error caused by the heterogeneity of the ore samples is also large. There are long processes and high consumption when determining the leaching conditions. Summary of the invention
[0003] Therefore, in view of the above-mentioned problems, the object of the present invention is to provide a method for determining the characteristics and process parameters of ion adsorption type rare earth leaching, which has a short process and low consumption.
[0004] A method for determining the concentration of a leaching agent for leaching ion-adsorption type rare earth minerals comprises the following steps:
[0005] The original rare earth mineral sample is dispersed in an aqueous solution to obtain a solution to be analyzed, and the liquid-to-solid ratio thereof is preset to R1;
[0006] Adding the leaching agent solution to the liquid to be analyzed several times to drip rare earth ions, and analyzing the rare earth concentration of the supernatant of the liquid to be analyzed after each dripping;
[0007] When the rare earth concentration of the supernatant after the Nth drip leaching increases by less than 1% compared with the rare earth concentration of the supernatant after the N-1th drip leaching, the drip leaching is stopped, so as to obtain the optimal leaching agent concentration C1 of the leaching agent for the native rare earth mineral sample at the liquid-solid ratio, wherein the optimal leaching agent concentration C1 is the concentration of the sum of the leaching agent solutions used from the 1st to the Nth times in the solution to be analyzed;
[0008] According to the following formula, the leaching concentration C2 of the leaching agent for the mineral of the native rare earth mineral sample when used for non-equilibrium leaching is calculated:
[0009]
[0010] Wherein, K is the correction coefficient, and the range of K is 0.1-0.6.
[0011] Preferably, the particle size of the native rare earth mineral sample is 200-800 mesh.
[0012] Preferably, the liquid-to-solid ratio R1 is 10-50.
[0013] Preferably, the method further comprises: the drip leaching of rare earth ions is performed on a zeta potential analyzer.
[0014] Preferably, the method further comprises: after dispersing the native rare earth mineral sample in an aqueous solution, measuring one, two or more of the zeta potential, pH value and conductivity value of the liquid to be analyzed.
[0015] Preferably, after each dripping, one, two or more of the zeta potential of the clay mineral particles in the suspension at equilibrium, the pH value and the conductivity of the solution are measured; and the liquid to be analyzed after the Nth dripping is filtered to obtain a filter cake, and the filter cake is redispersed in water to measure one, two or more of the zeta potential, pH value and conductivity of the suspension.
[0016] The invention solves the problems of long process, high consumption and large error when determining the leaching conditions in the existing on-column elution method; in addition, it can also simultaneously determine the specific method of reducing the amount of wastewater generated and reducing soil erosion.
[0017] Compared with the traditional column leaching method, the method of the present invention can realize continuous drip leaching without changing the mineral sample each time, solving the problems of long process and high consumption; further, the zeta potential, pH value, conductivity value at each leaching equilibrium and the zeta potential, pH value and pollutant concentration of the tailing particles after leaching rare earths in water can be measured simultaneously. Using these data, not only can the relationship between rare earth leaching efficiency and zeta potential, pH and conductivity be studied, the leaching exchange law be explored, the leaching reagent and its optimal concentration range be selected, but also the concentration of electrolytes and pollutants such as leached rare earths and heavy metals in the solution after each leaching, the pH of the solution and the amount of wastewater generated when the discharge standard is reached can be further determined. Since the zeta potential value of clay mineral particles is related to their suspension and dispersibility in water, and the suspension of clay minerals is related to the difficulty of soil and water loss of clay minerals, the amount of tailings wastewater generated and the risk of landslides and collapses after leaching rare earths by each leaching reagent can be evaluated, and specific methods for reducing soil and water loss can be proposed.
[0018] The more times water washing is required to meet the discharge standards, the more wastewater is generated.
[0019] If the absolute value of the Zeta potential of the clay mineral after leaching is larger than that of the original ore, it is easy to cause landslides. The closer its absolute value is to zero, the more stable it is and the less likely it is to cause landslides. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1: Relationship between the Zeta potential value of clay minerals and the size of clay mineral particles after equilibrium leaching and water leaching of three ore samples.
[0021] Figure 2 :Zeta potential of ion-adsorbing rare earth ore samples at each titration equilibrium when six sulfates were used as electrolytes at a certain concentration and then continuously dripped.
[0022] Figure 3 : The pH of the ion-adsorbing rare earth ore sample was determined at each titration equilibrium by continuous dripping with six sulfates as electrolytes at a certain concentration.
[0023] Figure 4 :The conductivity values of the ion-adsorbing rare earth ore samples at each titration equilibrium when six kinds of sulfates were used as electrolytes at a certain concentration and then continuously dripped.
[0024] Figure 5 : The rare earth leaching rate of Dingnan ion adsorption type rare earth ore sample at each titration equilibrium when six kinds of sulfates were used as electrolytes at a certain concentration and then continuously dripped.
[0025] Figure 6 : Zeta potential of Longnan ion-adsorption rare earth ore sample at each titration equilibrium when six sulfates were used as electrolytes at a certain concentration and dripped continuously.
[0026] Figure 7 : The pH of each titration equilibrium of Longnan ion-adsorption rare earth ore sample was continuously dripped with six sulfates as electrolytes at a certain concentration.
[0027] Figure 8 :The conductivity values of Longnan ion-adsorption rare earth ore samples at each titration equilibrium when six sulfates were used as electrolytes at a certain concentration and dripped continuously.
[0028] Fig. 9 : The rare earth leaching rate of Longnan ion-adsorption rare earth ore sample at each titration equilibrium when six sulfates were used as electrolytes at a certain concentration and then continuously drip-leached.
[0029] Fig.10 :Zeta potential of ion-adsorbing rare earth ore samples at each titration equilibrium when seven chlorides were used as electrolytes at a certain concentration and then continuously dripped.
[0030] Fig.11 :The pH of the ion-adsorbing rare earth ore sample at each titration equilibrium was determined by continuous titration of seven chlorides as electrolytes at a certain concentration.
[0031] Fig.12 :The conductivity values of the ion-adsorbing rare earth ore samples at each titration equilibrium were obtained by continuous drip leaching of the samples with seven chlorides as electrolytes at a certain concentration.
[0032] Fig.13:The rare earth leaching rate of the ion-adsorbing rare earth ore sample was continuously dripped with seven chlorides as electrolytes at a certain concentration at each titration equilibrium.
[0033] Fig.14 : Zeta potential of Longnan ion-adsorption rare earth ore sample at each titration equilibrium when seven chlorides were used as electrolytes at a certain concentration and dripped continuously.
[0034] Fig.15 : The pH of each titration equilibrium of Longnan ion-adsorption rare earth ore sample was continuously dripped with seven chlorides as electrolytes at a certain concentration.
[0035] Fig.16 :The conductivity values of Longnan ion-adsorption rare earth ore samples at each titration equilibrium when seven chlorides were used as electrolytes at a certain concentration and dripped continuously.
[0036] Fig.17 : The rare earth leaching rate of Longnan ion-adsorption rare earth ore sample at each titration equilibrium when seven chlorides were used as electrolytes at a certain concentration and then continuously drip-leached.
[0037] Fig.18 :Zeta potential of ion-adsorbing rare earth ore samples at each titration equilibrium when seven nitrates were used as electrolytes at a certain concentration and then continuously dripped.
[0038] Fig.19 :The pH of the ion-adsorbing rare earth ore sample was determined at each titration equilibrium by continuous dripping with seven nitrates as electrolytes at a certain concentration.
[0039] Fig. 20 :The conductivity values of the ion-adsorbing rare earth ore samples at each titration equilibrium when seven nitrates were used as electrolytes in continuous drip leaching at a certain concentration.
[0040] Fig.21 : The leaching rate of rare earth at each titration equilibrium when seven nitrates were used as electrolytes for continuous drip leaching of ion-adsorbed rare earth ore samples at a certain concentration.
[0041] Fig. 22 : Zeta potential of Longnan ion-adsorption rare earth ore sample at each titration equilibrium when seven nitrates were used as electrolytes at a certain concentration and dripped continuously.
[0042] Fig.23 : The pH of each titration equilibrium of Longnan ion-adsorption rare earth ore sample was continuously dripped with seven nitrates as electrolytes at a certain concentration.
[0043] Fig.24 :The conductivity values of Longnan ion-adsorption rare earth ore samples at each titration equilibrium when seven nitrates were used as electrolytes at a certain concentration and dripped continuously.
[0044] Fig.25 : The rare earth leaching rate of Longnan ion-adsorption rare earth ore sample at each titration equilibrium when seven nitrates were used as electrolytes at a certain concentration and then continuously drip-leached.
[0045] Fig.26 : Zeta potential of tailings after continuous drip leaching of Dingnan ion-adsorbed rare earth ore samples with six sulfates as electrolytes at certain concentrations.
[0046] Fig. 27 : Conductivity of the solution after continuous drip leaching of Dingnan ion-adsorbing rare earth ore samples with six sulfates as electrolytes at a certain concentration.
[0047] Fig.28 : Zeta potential of tailings after continuous drip leaching of Longnan ion-adsorption rare earth ore samples with six sulfates as electrolytes at certain concentrations.
[0048] Fig.29 : Conductivity of the solution after continuous drip leaching of Longnan ion-adsorption rare earth ore samples with six sulfates as electrolytes at a certain concentration.
[0049] Fig.30 : Zeta potential of tailings after continuous drip leaching of Dingnan ion-adsorbing rare earth ore samples with seven chlorides as electrolytes at certain concentrations.
[0050] Fig.31 : Conductivity values of tailings after continuous drip leaching of Dingnan ion-adsorption rare earth ore samples with seven chlorides as electrolytes at certain concentrations.
[0051] Fig.32 : Zeta potential of tailings after continuous drip leaching of Longnan ion-adsorption rare earth ore samples with seven chlorides as electrolytes at certain concentrations.
[0052] Fig.33 : Conductivity values of tailings after continuous drip leaching of Longnan ion-adsorption rare earth ore samples with seven chlorides as electrolytes at certain concentrations.
[0053] Fig.34 : Zeta potential of tailings after continuous drip leaching of Dingnan ion-adsorbing rare earth ore samples with seven nitrates as electrolytes at certain concentrations.
[0054] Fig.35 : Conductivity values of tailings after continuous drip leaching of Dingnan ion-adsorption rare earth ore samples at certain concentrations using seven nitrates as electrolytes.
[0055] Fig.36 : Zeta potential of tailings after continuous drip leaching of Longnan ion-adsorption rare earth ore samples with seven nitrates as electrolytes at certain concentrations.
[0056] Fig.37 : Conductivity values of tailings after continuous drip leaching of Longnan ion-adsorption rare earth ore samples with seven nitrates as electrolytes at certain concentrations.
[0057] Fig.38 :: Rare earth leaching rate of Dingnan ion-adsorption type rare earth ore sample when six inorganic salts are used as electrolytes at a certain concentration and the liquid-to-solid ratio is 1:1.
[0058] Fig.39 :: Rare earth leaching rate of Longnan ion-adsorption type rare earth ore sample when six inorganic salts are used as electrolytes at a certain concentration and the liquid-to-solid ratio is 1:1.
[0059] Fig.40 ::Rare earth leaching rates of Dingnan ion-adsorption type rare earth ore samples when five inorganic salts were used as electrolytes at certain concentrations and the liquid-to-solid ratios were 1:1 and 2:1. DETAILED DESCRIPTION
[0060] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0061] In addition, the descriptions of "first", "second", etc. in the present invention are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0062] The method of ionic rare earth full leaching and rare earth content determination published in "Rare Metals" in 1985 proposed the problem of eliminating the inhomogeneity of ore samples by ore blending. Although the workload of sample processing has increased, the reproducibility of the determination results is good, the error range has been greatly reduced, and it has been applied in the determination of the rare earth content of the original ore. However, in the selection of leaching reagents and conditions, most studies did not adopt the ore blending method. In addition, there are specific requirements for the liquid-solid ratio during leaching when selecting leaching conditions. The error caused by the inhomogeneity of ore samples will be greater. Therefore, some contradictory reports have appeared in the study of the effects of the types of leaching reagents and their concentrations on leaching efficiency. It fluctuates, and even the order is reversed. It is difficult to determine whether it is a problem with the leaching agent or a problem with the inhomogeneity of the column layer.
[0063] In addition, when optimizing the leaching conditions, in addition to considering the leaching rate of the leaching agent for rare earths, the safety performance of the tailings should also be considered. The safety of tailings is mainly considered from two aspects: pollutant emissions and soil erosion. In our previous research, we proposed a new method to study the relationship between the type and concentration of leaching agents and leaching efficiency based on the change of zeta potential of clay minerals in leached tailings. Zeta potential can be used to explain many surface phenomena, such as particle accumulation and deposition. By comparing the effects of different leaching agents and their concentration changes on the leaching rate and zeta potential of rare earths, it was found that for a specific agent, as the concentration changes, the leaching efficiency and zeta potential also change accordingly, and there is a linear relationship between them. The slope of the straight line is related to the leaching capacity of the leaching agent. Based on this, the leaching capacity of different leaching agents for rare earths can be compared and judged, and an evaluation method for leaching efficiency and tailings landslide risk based on Zeta potential measurement is proposed. In terms of experimental methods, leaching experiments, determination of rare earth concentration and tailings zeta potential need to be performed separately under each concentration condition. Therefore, for each reagent, a series of experiments need to be performed. The sample volume and reagent consumption are relatively large. In addition, due to the uniformity of the samples, parallel experiments are required to calculate the experimental errors, which increases the workload.
[0064] The applicant further studied the effect of the liquid-to-solid ratio in the suspension on the zeta potential during the experiment and the determination results of the leached rare earth. It is proved that reducing the liquid-to-solid ratio can increase the absolute value of the measured zeta potential and reduce the experimental error. At the same time, the amount of rare earth leached is also increased, which is also conducive to reducing the error of rare earth concentration determination. In this way, after each leaching, it is not necessary to use all or most of the leaching solution for the determination of rare earth concentration. Only a small amount of solution is needed to complete the determination of rare earth concentration. Based on this, a continuous drip leaching method for determining the ion adsorption type rare earth leaching characteristics and optimizing the leaching conditions is proposed. For each reagent, only one continuous titration leaching experiment is needed to determine the relationship between the leached rare earth concentration and the concentration of the leaching agent. At the same time, the zeta potential of the clay mineral, the pH and conductivity of the solution are determined, and the main characteristic parameters of the leaching process can be determined. By comparing the leaching experimental results of different leaching agents, the leaching capacity and order of each leaching agent can be determined. Provide a direct basis for selecting leaching agents and concentration conditions.
[0065] The present application provides a method for determining the concentration of a leaching agent for leaching ion-adsorption type rare earth minerals, comprising the following steps:
[0066] The original rare earth mineral sample is dispersed in an aqueous solution to obtain a solution to be analyzed, and the liquid-to-solid ratio thereof is preset to R1;
[0067] Adding the leaching agent solution to the liquid to be analyzed several times to drip rare earth ions, and analyzing the rare earth concentration of the supernatant of the liquid to be analyzed after each dripping;
[0068] When the rare earth concentration of the supernatant after the Nth drip leaching increases by less than 1% compared with the rare earth concentration of the supernatant after the N-1th drip leaching, the drip leaching is stopped, so as to obtain the optimal leaching agent concentration C1 of the leaching agent for the native rare earth mineral sample at the liquid-solid ratio, wherein the optimal leaching agent concentration C1 is the concentration of the sum of the leaching agent solutions used from the 1st to the Nth times in the solution to be analyzed;
[0069] According to the following formula, the leaching concentration C2 of the leaching agent for the mineral of the native rare earth mineral sample when used for non-equilibrium leaching is calculated:
[0070]
[0071] Wherein, K is the correction coefficient, and the range of K is 0.1-0.6.
[0072] Preferably, the particle size of the native rare earth mineral sample is 200-800 mesh.
[0073] Preferably, the liquid-to-solid ratio R1 is 10-50.
[0074] Preferably, the method further comprises: the drip leaching of rare earth ions is performed on a zeta potential analyzer.
[0075] Preferably, the method further comprises: after dispersing the native rare earth mineral sample in an aqueous solution, measuring one, two or more of the zeta potential, pH value and conductivity value of the liquid to be analyzed.
[0076] Preferably, after each dripping, one, two or more of the zeta potential of the clay mineral particles in the suspension at equilibrium, the pH value and the conductivity of the solution are measured; and the liquid to be analyzed after the Nth dripping is filtered to obtain a filter cake, and the filter cake is redispersed in water to measure one, two or more of the zeta potential, pH value and conductivity of the suspension.
[0077] The invention solves the problems of long process, high consumption and large error when determining the leaching conditions in the existing on-column elution method; in addition, it can also simultaneously determine the specific method of reducing the amount of wastewater generated and reducing soil erosion.
[0078] Compared with the traditional column leaching method, the method of the present invention can realize continuous drip leaching without changing the mineral sample each time, solving the problems of long process and high consumption; further, the zeta potential, pH value, conductivity value at each leaching equilibrium and the zeta potential, pH value and pollutant concentration of the tailing particles after leaching rare earths in water can be measured simultaneously. Using these data, not only can the relationship between rare earth leaching efficiency and zeta potential, pH and conductivity be studied, the leaching exchange law can be explored, the leaching reagent and its optimal concentration range can be selected, and the concentration of electrolytes and pollutants such as leached rare earths and heavy metals in the solution after each leaching and the pH of the solution can be further determined, and the amount of wastewater generated when the discharge standard is reached. Since the zeta potential value of clay mineral particles is related to their suspension and dispersibility in water, and the suspension of clay minerals is related to the difficulty of soil and water loss of clay minerals, the amount of tailings wastewater generated and the risk of landslides after leaching rare earths by each leaching reagent can be evaluated, and a specific method for reducing soil and water loss can be proposed.
[0079] The more times water washing is required to meet the discharge standards, the more wastewater is generated.
[0080] If the absolute value of the Zeta potential of the clay mineral after leaching is larger than that of the original ore, it is easy to cause landslides. The closer its absolute value is to zero, the more stable it is and the less likely it is to cause landslides.
[0081] The ion-adsorption rare earth ores used in the examples were all taken from Dingnan and Longnan. The samples were prepared from the ore samples by wet screening, and clay particles larger than 800 mesh were screened out and dried and ground at 80° C. for later use.
[0082] Unless otherwise specified, the volume of each electrolyte titration in the examples is 2 ml except for the sodium salt which is 4 ml. In the process of continuous dripping, after each titration reaches equilibrium, the supernatant of the corresponding titration volume is taken to analyze the rare earth content. The rare earth content is determined by azoarsenazo III spectrophotometry.
[0083] In this experiment, the calculation of rare earth leaching rate is based on the leaching rate of the maximum rare earth content in each ore sample as 100%. The maximum rare earth content of Dingnan ore sample is 2039.38ug / g, and the maximum rare earth content of Longnan ore sample is 1219.6ug / g.
[0084] Example 1
[0085] Investigate the relationship between Zeta potential value, clay mineral particle size and solid-liquid ratio during equilibrium leaching
[0086] To investigate the relationship between the Zeta potential value and the size of clay mineral particles during equilibrium leaching: three ion adsorption rare earth ore samples of Dingnan, Anyuan and Longnan with mesh sizes of 200-800 and larger than 800 were taken, and equilibrium leaching was performed with 2% ammonium sulfate at a solid-liquid ratio of 1:5. The Zeta potential values of clay minerals were measured when the leaching reached equilibrium and after water leaching. The experimental results are shown in the figure below. Figure 1 From the experimental results, it can be seen that, whether in the leaching process or in the water washing process, for these three ore samples, the Zeta potential of the clay ore samples larger than 800 mesh is larger than 200-800 mesh.
[0087] To explore the relationship between the Zeta potential value and the solid-liquid ratio during equilibrium leaching: Dingnan adsorption-type rare earth ore samples larger than 800 mesh were taken, and equilibrium leaching was performed with 2% ammonium sulfate at a solid-liquid ratio of 5%, 6%, 7%, 8%, 9%, and 10%, and the Zeta potential value of the clay mineral was measured when the leaching reached equilibrium. The experimental results are as follows Figure 2 ,From the experimental results, we can see that with the increase of solid content, the absolute value of Zeta increases, and there is a good linear relationship.
[0088] Combining the results of (1) and (2), in order to reduce experimental errors, we selected clay samples larger than 800 mesh and conducted continuous drip leaching experiments on them with a solid-liquid ratio of 10%.
[0089] Example 2
[0090] Comparison of the rare earth leaching rates of two ion-adsorption rare earth ore samples of Dingnan and Longnan by continuous drip leaching of six kinds of sulfates as electrolytes at certain concentrations: 25 grams of Dingnan / Longnan clay ore samples with a mesh size greater than 800 were dispersed in 250ml of aqueous solution, and balanced and shaken in a constant temperature oscillation tank at 25℃ for 30 minutes, and then their zeta potential, pH value and conductivity were measured on a zeta potential analyzer; then, a certain concentration of sulfate solution (0.9mol / lNa2SO4, 0.6ml / lK2S O4, 0.6mol / l(NH4)2SO4, 0.6mol / lZnSO4, 0.6mol / lMgSO4, 0.05mol / lAl2(SO4)3) were used to continuously drip leaching rare earth for several times, and the characteristic parameters such as zeta potential, pH value, conductivity, etc. were measured when each drip leaching reached equilibrium. The corresponding volume of supernatant was taken to analyze the rare earth concentration; the rare earth leaching rate was calculated and the electrolyte concentration in the equilibrium solution was plotted to determine the optimal leaching reagent type and concentration conditions. The experimental results are as follows Figure 2-Figure 10, the experimental results show that for Dingnan and Longnan ore samples, aluminum sulfate has the best leaching effect. The optimal concentration of aluminum sulfate in Dingnan ore samples is 2.8mmol / l, and the optimal concentration of aluminum sulfate in Longnan ore samples is 2.4mmol / l. The optimal concentrations of other sulfates are as follows: Dingnan ore samples: the optimal concentration of ammonium sulfate is 28.8mmol / l, the optimal concentration of potassium sulfate is 33.6mmol / l, the optimal concentration of magnesium sulfate is 48mmol / l, the optimal concentration of zinc sulfate is 52.8mmol / l, and the optimal concentration of sodium sulfate is 158.4mmol / l. Longnan ore samples: the optimal concentration of ammonium sulfate is 33.6mmol / l, the optimal concentration of potassium sulfate is 28.8mmol / l, the optimal concentration of magnesium sulfate is 52.8mmol / l, the optimal concentration of zinc sulfate is 52.8mmol / l, and the optimal concentration of sodium sulfate is 158.4mmol / l.
[0091] Example 3
[0092] Comparison of rare earth leaching rates of two ion adsorption type rare earth ores of Dingnan and Longnan by continuous drip leaching of seven chlorides as electrolytes at a certain concentration: the electrolyte solutions used were 1.8mol / lNaCl, 1.8mol / lKCl, 1.2mol / lNH4Cl, 0.45mol / lCaCl2, 0.6mol / lZnCl2, 0.6mol / lMgCl2, 0.1mol / lAlCl3. The experimental results are shown in the figure. Figure 11-Figure 18 The experimental results show that for Dingnan and Longnan ore samples, aluminum chloride has the best leaching effect. The optimal concentration of aluminum chloride in Dingnan ore samples is 8.8mmol / l, and the optimal concentration of aluminum chloride in Longnan ore samples is 5.6mmol / l. The optimal concentrations of other chlorides are as follows: Dingnan ore samples: the optimal concentration of ammonium chloride is 105.6mmol / l, the optimal concentration of potassium chloride is 115.2mmol / l, the optimal concentration of calcium chloride is 43.2mmol / l, the optimal concentration of magnesium chloride is 57.6mmol / l, the optimal concentration of zinc chloride is 57.6mmol / l, and the optimal concentration of sodium chloride is 345.6mmol / l. Longnan ore samples: the optimal concentration of ammonium chloride is 96mmol / l, the optimal concentration of potassium chloride is 100.8mmol / l, the optimal concentration of calcium chloride is 43.2mmol / l, the optimal concentration of magnesium chloride is 57.6mmol / l, the optimal concentration of zinc chloride is 57.6mmol / l, and the optimal concentration of sodium chloride is 345.6mmol / l.
[0093] Example 4
[0094] Comparison of the rare earth leaching amount and rare earth leaching rate of two ion adsorption type rare earth ores of Dingnan and Longnan by continuous drip leaching of seven nitrates as electrolytes at a certain concentration: the electrolyte solutions used were 1.8mol / lNaNO3, 1.8mol / lKNO3, 1.2mol / lNH4NO3, 0.45mol / lCa(NO3)2, 0.6mol / lZn(NO3)2, 0.6mol / lMg(NO3)2, 0.1mol / lAl(NO3)3. The experimental results are shown in Figure 19-Figure 26 The experimental results show that for Dingnan and Longnan ore samples, aluminum nitrate has the best leaching effect. The optimal concentration of aluminum nitrate in Dingnan ore samples is 7.2mmol / l, and the optimal concentration of aluminum nitrate in Longnan ore samples is 5.6mmol / l. The optimal concentrations of other nitrates are as follows: Dingnan ore samples: the optimal concentration of ammonium nitrate is 115.2mmol / l, the optimal concentration of potassium nitrate is 115.2mmol / l, the optimal concentration of calcium nitrate is 39.6mmol / l, the optimal concentration of magnesium nitrate is 57.6mmol / l, the optimal concentration of zinc nitrate is 57.6mmol / l, and the optimal concentration of sodium nitrate is 345.6mmol / l. Longnan ore samples: the optimal concentration of ammonium nitrate is 115.2mmol / l, the optimal concentration of potassium nitrate is 115.2mmol / l, the optimal concentration of calcium nitrate is 43.2mmol / l, the optimal concentration of magnesium nitrate is 57.6mmol / l, the optimal concentration of zinc nitrate is 57.6mmol / l, and the optimal concentration of sodium nitrate is 345.6mmol / l.
[0095] Example 5
[0096] Comparison of electrolyte concentration and suspension of clay particles after tailings leaching with different leaching agents: After the leaching, filter; re-disperse the filter cake into 250ml of water, stir and disperse, measure the characteristic parameters such as Zeta potential, pH value, conductivity, observe the clarification, and take a certain volume of supernatant to analyze the rare earth and electrolyte concentrations.
[0097] The above steps were repeated three times to evaluate the amount of wastewater generated by the tailings being leached by rainwater after leaching rare earths with each leaching agent and the risk of soil erosion. The rare earth content in the tailings leached solution after drip leaching with different leaching agents is relatively small, so the conductivity value measured after stirring and dispersing can largely reflect the concentration of electrolytes in the leached solution, and the larger the conductivity value, the greater the electrolyte concentration; and the Zeta potential value measured after stirring and dispersing can largely reflect the suspension of clay particles. The larger the absolute value of the Zeta potential, the better the suspension of clay particles and the greater the risk of soil erosion.
[0098] The experimental results are as follows Figure 27-Figure 38The experimental results show that for the ion adsorption type ore samples in Dingnan and Longnan, the electrolyte concentrations of the tailings after drip leaching with different leaching agents are similar. The electrolyte concentrations of the tailings after drip leaching with different leaching agents are all: the concentration of the electrolyte in the solution after leaching is related to the concentration of the drip leaching electrolyte. The greater the drip leaching concentration, the greater the electrolyte concentration in the solution after leaching. The electrolyte concentrations in the solution after the first leaching are quite different, while the concentrations of each electrolyte in the solution after the second and third leaching are not much different, especially after the third leaching, the concentrations of each electrolyte in the solution are very close, and are not much different from the conductivity value of the original ore. For the suspension of clay particles after tailings leaching after drip leaching with different leaching agents: the suspension of clay particles after tailings leaching after drip leaching with electrolytes of different systems such as sulfate, chloride and nitrate is related to the cations of the drip leaching electrolyte, and the suspension of cations with the same valence is similar. The suspension of Longnan ore samples in sulfuric acid system, chlorination system and nitric acid system is K, Na, NH4>Mg, Zn, Ca>Al, while the suspension of Dingnan ore samples in chlorination system and nitric acid system is K, Na, NH4>Al>Mg, Zn, Ca, and in sulfuric acid system it is K, Na, NH4>Mg, Zn, Ca>Al.
[0099] Example 6
[0100] Ammonium sulfate, magnesium sulfate, aluminum sulfate, ammonium chloride, magnesium chloride, and aluminum chloride were selected as leaching agents, with a liquid-to-solid ratio of 1:1. Longnan and Dingnan ore samples below 20 mesh were taken for column elution experiments, and the effects of different leaching agents and different concentrations on the leaching efficiency of these two ore samples were compared. The experimental results are shown in the figure below. Fig.39 and Fig.40 The experimental results show that for Dingnan and Longnan ore samples, aluminum sulfate has the best leaching effect. The optimal concentration of aluminum sulfate for Dingnan ore samples is 33.3mmol / l, and the optimal concentration of aluminum sulfate for Longnan ore samples is 6.6mmol / l. The optimal concentrations of other leaching agents are as follows: Dingnan ore samples: the optimal concentration of magnesium sulfate is 192mmol / l, the optimal concentration of ammonium sulfate is 128mmol / l, the optimal concentration of calcium chloride is 192mmol / l, the optimal concentration of magnesium chloride is 192mmol / l, and the optimal concentration of ammonium chloride is 384mmol / l. Longnan ore samples: the optimal concentration of magnesium sulfate is 160mmol / l, the optimal concentration of ammonium sulfate is 96mmol / l, the optimal concentration of calcium chloride is 192mmol / l, the optimal concentration of magnesium chloride is 128mmol / l, and the optimal concentration of ammonium chloride is 320mmol / l. The order of on-column leaching effect is similar to that of continuous drip leaching.
[0101] Please refer to Table 1. After obtaining C1 by the method of the above embodiment, C2 is calculated according to the formula of the present invention. In addition, the optimal leaching agent concentration C0 is experimentally measured by the non-equilibrium leaching method. Comparing C2 with C0, it can be seen that the method of the present application is reliable for determining the leaching agent concentration for leaching ion adsorption type rare earth minerals.
[0102] Table 1
[0103] Ore samples Ore sample mesh <![CDATA[R1]]> Extraction agent <![CDATA[C1(mm / l)]]> <![CDATA[R2]]> K <![CDATA[C2(mm / l)]]> <![CDATA[C0(mm / l)]]> Dingnan 200-800 10 Ammonium sulfate 24 1 0.1-0.6 24-144 128 Dingnan More than 800 10 Ammonium sulfate 28.8 1 0.1-0.6 28.8-172.8 128 Dingnan More than 800 50 Ammonium sulfate 14.4 1 0.1-0.6 72-432 128 Dingnan More than 800 10 Ammonium sulfate 28.8 2 0.1-0.6 28.8-172 64 Dingnan More than 800 10 Ammonium chloride 105.6 1 0.1-0.6 105.6—633.3 384 Dingnan More than 800 10 Aluminum sulfate 2.8 2 0.1-0.6 1.4-8.4 6.66 Dingnan More than 800 10 Calcium chloride 43.2 1 0.1-0.6 43.2-259.2 192 Dingnan More than 800 10 Calcium chloride 43.2 2 0.1-0.6 43.2-259.2 192 Longnan More than 800 10 Ammonium sulfate 33.6 1 0.1-0.6 33.6-201.6 96 Longnan More than 800 10 Ammonium chloride 96 1 0.1-0.6 96-576 384 Longnan More than 800 10 Calcium chloride 43.2 1 0.1-0.6 43.2-259.2 192
[0104] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention specification under the inventive concept of the present invention, or directly or indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for determining the characteristics and process parameters of ion adsorption type rare earth leaching, characterized in that: The following steps are involved: Dispersing a native rare earth mineral sample in an aqueous solution to obtain a solution to be analyzed, wherein the liquid-to-solid ratio R1 is 10-50, and measuring one, two or more of the zeta potential, pH value, and conductivity value of the solution to be analyzed; Adding the leaching agent solution to the liquid to be analyzed several times to drip rare earth ions, analyzing the rare earth concentration of the supernatant of the liquid to be analyzed after each dripping, and measuring one, two or more of the zeta potential of clay mineral particles in the suspension, the pH value and the conductivity value of the solution at equilibrium; When the rare earth concentration of the supernatant after the Nth drip leaching increases by less than 1% compared with the rare earth concentration of the supernatant after the N-1th drip leaching, the drip leaching is stopped to obtain the optimal leaching agent concentration C1 of the leaching agent for equilibrium leaching of the native rare earth mineral sample at the liquid-to-solid ratio, and the optimal leaching agent concentration C1 is the concentration of the sum of the leaching agent solutions used from the 1st to the Nth time in the liquid to be analyzed; and the liquid to be analyzed after the Nth drip leaching is filtered to obtain a filter cake, the filter cake is redispersed in water, and one, two or more of the zeta potential, pH value, and conductivity of the suspension are measured.
2. The measuring method according to claim 1, characterized in that The particle size of the native rare earth mineral sample is 200-800 mesh.
3. The measuring method according to claim 1, characterized in that Also includes: The leaching of rare earth ions was carried out on a zeta potential analyzer.
4. The measuring method according to claim 1, characterized in that The particle size of the native rare earth mineral sample is greater than 800 meshes.
Citation Information
Patent Citations
Method for determining permeability and rare earth recovery rate of ion-adsorption-type rare earth deposit
CN104573210A
Real-time monitoring method for ion-type rare earth dump leaching seepage efficiency
CN112964611A